The impact of globalization on ethical leadership:a critical explanation from tawhidic paradigm - Nabi, Ashiqun; Sarif, Suhaimi Mhd (2012)
This paper explains the impact of globalization in ethical leadership. According to the theory, Globalization is an elimination of barriers to trade, communication, and cultural exchange. The theory behind globalization is that worldwide openness will promote the inherent wealth of all nations. The globalization includes in the four important areas (i.e. knowledge, business, government, and society) can give significant impact on ethical leadership. The study obtained the opinions of 25 MBA and MOM students from Graduate School of Management through a survey on the impact of globalization on ethical leadership. The study found that globalization has a significant impact on changing people’s perspective about the need to have ethical leadership in today’s transnational corporations. The informants viewed that the Tawhidic paradigm offers spiritual dimension to educate and nurture people to ethical and influential in leading the globalization and the future. Nevertheless, the results of the study are constrained by the size of the sample and robustness of the analysis.